Use of atropine in patients with chronotropic incompetence and poor exercise capacity during treadmill stress testing - Ihab Ahmed Mohamed; Gamal Hamed; Mervat M . Khalaf; Sherif Sabri (Cairo : Ihab Ahmed Mohamed, 2010)
Objective : Exercise stress test (EST) is one of the main diagnostic and prognostic tests for ischemic heart disease . However its usefulness depends on achieving target heart rate and then chronotropic incompetence and poor exercise capacity limits its utility . We evaluated the usefulness and accuracy of atropine administration during the EST to decrease the number of tests with inconclusive results in these patients
Thesis (M.Sc.) - Cairo University - Faculty of Medicine - Department of Critical Care Medicine
Issued also as CD
Keywords: Atropine; Chronotropic incompetence; ECG